Effectiveness and resource utilization of hospital-based contact tracing of patients and health care workers with COVID-19 at a tertiary teaching hospital in Thailand - Worapong Nasomsong; Dhitiwat Changpradub; Vasin Vasikasin (Elsevier, 2023)
Background: The benefits of contact tracing in health care workers (HCWs) and patients in hospital have rarely been evaluated. This study aimed to assess the yield of contact tracing in order to evaluate the usefulness of resource utilization. Methods: Data were collected from 1 April 2021 to 31 March 2022 at teaching hospital in Thailand. The team was notified if any HCW or patient admitted outside COVID-19 designated areas were tested positive. Those with high-risk exposure identified by the team needed to leave from work for 14 days and 2 PCR tests as early as possible and day 14 after the exposure. Result: A total of 4,292 HCWs and 422 patients were exposed to 575 COVID-19 cases and were identified as high-risk contacts, leading to 50,312 days of quarantine and 9,333 PCR tests. The secondary attack rate was 3.42%, which was more common in patients than in HCWs (OR = 1.82, 95%CI = 1.17-2.85, p = 0.0082). Close contact with patients had more secondary attack rates than with HCWs (OR = 1.51, 95%CI:1.01-2.25, p = 0.045). Among those who had close contact with patients, patients but not HCWs had increased risk of infection (OR = 2.86; 95%CI:1.24-6.62; p = 0.0138, OR = 1.06; 95%CI:0.63-1.77; p = 0.834, respectively). The positivity rate of high-risk close contact HCWs was 2.28 per 1,000 person-days after contact, as compared to the positivity rate of low-risk close contact with symptoms at 0.35 per 1,000 person-days during the same period. Conclusions: Hospital-based contact tracing could identify more infected HCWs than symptomatic testing alone. Identifying more infected HCWs could potentially prevent infection in both HCWs and patients.